The relationship between Personality Dimensions and Employee Job Commitment in Private Higher Learning Institutions - Saufi, Roselina Ahmad; Xin, Yang; Hongyun, Cheng; Berhan, Siti Aishah; Mamun, Abdullah al (International Review of Management and Marketing, 2017)
The objective of this study is to examine the effect of personality dimensions (i.e., extroversion, agreeableness, neuroticism, openness to experience, and conscientiousness) on job commitment. This study also aims to examine how gender differences and job level are associated with job commitment. This study adopted a cross-sectional design and collected quantitative data from 144 managerial and non-managerial level employees working in private higher learning institutes in Kota Kinabalu, Sabah, Malaysia. Findings of this study reveal that ‘conscientiousness' has a significant effect on job commitment. Among the moderators, ‘job level' also indicates a significant influence between personality dimensions and employees' job commitment. Private higher learning institutes in Malaysia should therefore focus on providing a supportive environment for employees to promote goal focus, dutifulness, self-discipline, and competence seeking behavior, which together leads to high job performance, career success, motivation, and job satisfaction. Keywords: Personality Dimensions, Job Commitment, Job level, Gender JEL Classifications: I23, M